Intermediate Algebra (12th Edition)

Published by Pearson
ISBN 10: 0321969359
ISBN 13: 978-0-32196-935-4

Chapter 4 - Section 4.1 - Integer Exponents and Scientific Notation - 4.1 Exercises: 91

Answer

a. B. 3 b. D. -3 c. D. -3 d. B. 3

Work Step by Step

According to the definition of negative exponents $a^{-n}=\frac{1}{a^{n}}$ (where $a\ne0$). Therefore, a. $(\frac{1}{3})^{-1}=\frac{1}{(\frac{1}{3})}=3$ b. $(-\frac{1}{3})^{-1}=\frac{1}{(-\frac{1}{3})}=-3$ c. $-(\frac{1}{3})^{-1}=-\frac{1}{(\frac{1}{3})}=-3$ d. $-(-\frac{1}{3})^{-1}=-(\frac{1}{-\frac{1}{3}})=-(-3)=3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.